The THE RELATIONSHIP BETWEEN SELF EFFICACY AND SPIRITUAL WELL-BEING WITH THE USE OF COPING STRATEGIES IN PEOPLE WITH HIV (ODHIV) - Sukmawati, Lina; Azzam, Rohman; Yunitri, Ninik; Rayasari, Fitrian; Novianti, Dian; Maemun, Siti (Jurnal Ilmiah Keperawatan IMELDA, 2025)
HIV infection continues to be a significant public health problem worldwide, including Indonesia, with impacts spanning social, economic, and cultural aspects. People living with HIV (PLHIV) are faced with various pressures and are in dire need of coping strategies. This study aimed to determine the relationship between self-efficacy and spiritual well-being with the use of coping strategies in PLHIV. This study is an analytic study with a cross sectional approach. A sample of 39 ODHIV was selected using purposive sampling method. Data were collected by filling out the GSES questionnaire to assess self-efficacy, the SWBS questionnaire to measure spiritual well-being, and the BRIEF RCOPE questionnaire to determine coping strategies. Logistic regression multinomial inferencial test found no association between self-efficacy and spiritual well-being with the use of coping strategies. Most were male (76.9%), high school education level (64.1%), and married (59%). Descriptive analysis obtained respondents who used problem-oriented coping strategies (28.2%); emotion-oriented (38.5%); and religious-oriented (33.3%). Multinomial logistic regression test showed no significant association between self-efficacy and the use of coping strategies and no association between spiritual well-being and coping strategies (p-value > 0.05). Spiritual aspects are important to consider as they can be a source of coping and motivation to help patients cope with sudden illness and reduce the level of pain due to the perceived condition so as to quickly move towards healing. Nurses need to apply nursing care using coping instruments, comprehensively from the assessment process to the evaluation process.